2001
DOI: 10.2307/2673929
|View full text |Cite
|
Sign up to set email alerts
|

Bank Ownership and Efficiency

Abstract: China is reforming its banking system, partially privatizing and taking on minority foreign ownership of three of its dominant ''Big Four" state-owned banks. This paper helps predict the effects by analyzing the efficiency of Chinese banks over 1994-2003. Findings suggest that Big Four banks are by far the least efficient; foreign banks are most efficient; and minority foreign ownership is associated with significantly improved efficiency. We present corroborating robustness checks and offer several credible m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
289
2
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(333 citation statements)
references
References 75 publications
31
289
2
11
Order By: Relevance
“…Thus, we notice that the public banks are inefficient as compared to the private and joint venture/foreign banks. This result is consistent with the study of Altunbas et al (2001) for German banks.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, we notice that the public banks are inefficient as compared to the private and joint venture/foreign banks. This result is consistent with the study of Altunbas et al (2001) for German banks.…”
Section: Resultssupporting
confidence: 82%
“…Many studies in bank efficiency use translog function to represent technology of production. However, Mithell and Onvural (1996), Berger, Leusner, and Mingo (1997) and Altunbas, Evans, andMolyneux (2001), Vennet (2002), Carbo, Gardener and Williams (2002) noted that augmented translog function, or fourier flexible (FF) form offers better approximation of the bank's unknown functional form. In summary, they concluded that adding trigonometrical terms to translog function to form flexible function is very effective to tackle down the problem of unknown multivariate function without misspecification.…”
Section: Methodsmentioning
confidence: 99%
“…First, with respect to efficiency: The empirical evidence stemming from Altunbas et al (2001) illustrate that mutual banks are not less efficient than their counterparts. Hansmann (1996) highlights the important role played by mutual banking institutions in the development of the U.S. financial system during the nineteenth century where they were equally competitive to stockholder owned banks.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…This result could be due to soft budget constraints of public banks, but no causal links are tested in this study. At the same time, there is evidence that public banks operate as efficiently as their competitors (Altunbas, Evans, and Molyneux, 2001), which is not consistent with the hypothesis that public banks operate with a soft budget constraint. Since public banks play an important role in providing state aid and are a means by which the politician can pursue economic policy, we believe that a comparison between public and private banks neglects the fact that the objectives of public banks are different from those of private banks.…”
Section: Introductionmentioning
confidence: 51%